Creating Metacognitive Awareness in the Lab: Outcomes for Preservice Science Teachers - (:unkn) unknown (MODESTUM LTD, 2013)
This study investigated the influence of metacognitive guidance on pre-service science teachers' scientific knowledge, science process skills, and views about the nature of science. The sample included 48 pre-service science teachers taking a first-year chemistry laboratory course in a public university in Turkey. During the 11-week course, the students conducted 11 experiments. Four scales were administered to a control group and an experimental group as pre- and post-tests. Differently from control group, experimental group discussed the experimental design and completed a reflection form before and after each experiment. Moreover, experimental group answered questions about daily life implications. Results indicate that the inclusion of metacognitive guidance helped the students in the experimental group to improve their process skills and conceptual understanding.
Keywords: metacognitive awareness; learning outcomes; preservice science teachers; PROCESS SKILLS; INQUIRY; CONCEPTIONS